Keep the city clean. The ambivalent ethics of ownership in urban routine and non-violent protest in Moscow. - Bikbov, Alexander (Routledge, 2021)
The chapter puts forward two major topics interconnected in Moscow city management and civic ethics of the last decade. The first deals with the sense of the citizens’ “own” place in the top-down managed city and mainly expressed in grassroot practices, starting from individual flower planting in the yards of panel buildings and coming up to procedural protest against abusive construction projects. “One’s own” place is constructed here as explicitly a-political, with a clear focus on cleanness boosted by both top-down municipal communication and daily sensibilities widely shared from below. In this context, the chapter discusses procedural novelties of distant and “nice” participatory regimes in district decision-making that are destined to transform the core public of urban discussion, its style and effects. The second topic concerns urban ethics of civic protest studied during street rallies and Occupy-like camps in Moscow, in 2011–2017. Dispositions framing “one’s own,” “clean” and “tidy” place are observed in a space autonomously managed by a protest neighborhood and targeted by police control. In this context, the research clears out the link between tidiness and repression exercised by the protesters themselves. Such normalizing practices as hygienic codes applied to common meals, volunteer cleaning raids and chasing homeless people from the Okkupay camps are closer examined as expressions of the ambiguous ethical disposition brought forth with the idea of clean city.
Keywords: Stadtpolitik; Sauberkeit; Bürgerbeteiligung; Stadthygiene; Protestbewegung; Zivilgesellschaft; Raumaneignung; Occupy-Bewegung